Factors controlling the growth rate, carbon and oxygen isotope variation in modern calcite precipitation in a subtropical cave, Southwest China. (1st April 2016) - Pu, Junbing; Wang, Aoyu; Shen, Licheng; Yin, Jianjun; Yuan, Daoxian; Zhao, Heping
Highlights: δ 18 O-VPDB and δ 13 C-VPDB in modern calcite precipitates shows clear seasonal variation. Isotope kinetic fractionation occurs between parent drip water and depositing calcite. Kinetic fractionation amplifies the equilibrium fractionation value of calcite δ 18 O (by ∼1.5‰) and δ 13 C (by ∼1.7‰). Abstract: A prerequisite for using cave speleothems to reconstruct palaeoenvironmental conditions is an accurate understanding of specific factors controlling calcite growth, in particular the isotopic partitioning of oxygen (δ 18 O) and carbon (δ 13 C) which are the most commonly used proxies. An in situ monitoring study from April 2008 to September 2009 at Xueyu Cave, Chongqing, SW China, provides insight into the controls on calcite growth rates, drip water composition, cave air parameters and δ 18 O and δ 13 C isotopic values of modern calcite precipitation. Both cave air P CO2 and drip water hydrochemical characteristics show obvious seasonality driven by seasonal changes in the external environment. Calcite growth rates also display clear intra-annual variation, with the lowest values occurring during wet season and peak values during the dry season. Seasonal variations of calcite growth rate are primarily controlled by variations of cave air P CO2 and drip water rate. Seasonal δ 18 O-VPDB and δ 13 C-VPDB in modern calcite precipitates vary, with more negative values in the wet season than in the dry season. Strong positive correlation of δ 18 O-VPDB vs. δ 13 C-VPDB is due to simultaneous enrichment of both isotopes in the calcite. This correlation indicates that kinetic fractionation occurs between parent drip water and depositing calcite, likely caused by the variations of cave air P CO2 and drip rate influenced by seasonal cave ventilation. Kinetic fractionation amplifies the equilibrium fractionation value of calcite δ 18 O (by ∼1.5‰) and δ 13 C (by ∼1.7‰), which quantitatively reflects surface conditions during the cave ventilation season. These results indicate that the cave monitoring of growth rate and δ 18 O and δ 13 C of modern calcite precipitation are necessary in order to use a speleothem to reconstruct palaeoenvironment.